Spreadable ricotta cheese with hydrocolloids: Effect on physicochemical and rheological properties. (July 2019) - Rubel, Irene A.; Iraporda, Carolina; Gallo, Alicia; Manrique, Guillermo D.; Genovese, Diego B.
Abstract: Ricotta cheese was selected to develop a novel food product. Ricotta is easily obtained from the precipitation of whey and milk proteins, through the application of heat and acidification. This product is characterised by its compact, finely granulated and crumbly mass of limited shelf life. Unlike the conventional methods for ricotta elaboration, a novel processing step was introduced to improve spreadability. The effect of hydrocolloids addition on physicochemical, mechanical and rheological properties was evaluated during storage. Hydrocolloids had a positive effect on the cheese matrix regarding microstructure and rheological properties. Samples showed acceptable physicochemical properties (compared with the control) during storage. Addition of hydrocolloids attenuated syneresis. Preliminary results showed that the best formulation was ricotta cheese containing high gelification capacity gelatin. Results of this study may contribute to the development of a novel dairy product.